Sukuk Reduces Risk of Corruption and Theft of Funds - Sri Rahmany (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2018)
This paper aims to determine the importance of the structure of Sukuk through the creation of Special Purpose Vehicles (SPVs) provides better transparency thereby reducing corruption and wastage as productive assets must be put to work in order to generate rental incomes for investors, rather than disappearing into offshore banking centres or participating in deliberately overpriced projects. The paper relies on The 2014 report makes interesting reading with Denmark, New Zealand and Finland ranked as the least corrupt countries and unfortunately a host of OIC countries coming out towards the wrong side of index, with the notable exception of the UAE and Qatar which rank 25 and 26 respectively, better than the likes of France, Portugal and Poland. The results show that Corruption and abuse of state funds affect many countries and Organisation of Islamic Cooperation (OIC) countries are no exception. Corruption has a devastating impact for many reasons, one of which is whilst funds are siphoned off abroad, the debt remains on the countries balance sheet and accrues interest charges, compounding larger year after year. The results In addition to the traditional benefits of sukuk, such as diversifying an investor base and accessing investors who do not invest in interest-based bonds, a less discussed value add of sukuk is its structure, particularly the Ijara structure which to a greater deal over conventional bonds prevents the wastage of funds through corruption and theft. This paper is a pioneer study undertaking about Sukuk Reduces Risk of Corruption and Theft of Funds